Achieving Competitiveness through Analyzing Supply Chain: A Test of Political Stakeholder’s Action in Readymade Garment (RMG) Industry of Bangladesh - Nuruzzaman, Md.; Chowdhury, Md. Maruf Hossan; Quaddus, Mohammed; Jeeva, Ananda (Institute for Research and Community Service, Petra Christian University, 2013)
The textile and clothing (also known as garment) is one of the oldest and largest export industries in the world. As many competitors came into this market after abolition of quota system, achieving competitiveness has risen as a top prioritised issue in the RMG industry of Bangladesh. This study was designed to address research question as to how the external stakeholders influence the internal stakeholder of RMG supply chain to improve competitiveness. The principles of stakeholder and resource dependence theory have been used for this study to develop testable hypothesis. The data were collected from the RMG industry of Bangladesh. This study applies the quantitative research approach. Data were analyzed by using Partial Least Squire (PLS) based structural Equation modeling (SEM) tool. The result from PLS graph showed that all the hypotheses are supported. The study concludes with implications for improving supply chain and achieving competitiveness. The discussion and implications on the findings are discussed in details.